SULFUR CONTAINING MINERAL WATER AS A DIETARY FACTOR CHALLENGING THE PHASE II DETOXIFICATION ENZYMES IN HUMAN INTESTINAL CELLS - Todorka Sokrateva; Oskan Tasinov; Stefka Stoeva; Diana Ivanova; Neshe Nazifova-Tasinova; Milka Nashar (Journal of IMAB, 2022)
Introduction: According to the scientific literature, sulfur contained in various foods and medicines is almost completely absorbed in the gastrointestinal tract. However, the role of sulfur containing mineral waters as a dietary source of sulfur still remains unrevealed. The focus of this study was the effect of sulfurous mineral water from two public fountains on the territory of Varna town on the expression rates of enzymes involved in the processes of sulfonation in human intestinal cells. Methods: Human intestinal epithelial cells were incubated with different percentage content of sulfurous mineral water in the growth medium. Cell viability was measured by the MTT test, and three concentrations of mineral water were chosen for gene expression analyses. The cells were treated with water samples with different residence times after filling: 24 hours, 3 and 7 days. Messenger RNA levels of two sulfotransferases isoforms (SULT1A1 and SULT1A3) and 3′-phosphoadenosine-5′-phosphosulfate synthase 1 (PAPSS1) were measured. Results: Significantly increased mRNA levels of both sulfotransferases were measured in cells treated with 24-hours samples from the two fountains. This stimulatory effect was dependent on the percentage content of mineral water in the culture medium. Despite the stimulated expression of sulfotransferases, higher volume concentrations of 24-hour samples of mineral water significantly inhibited the gene expression of PAPSS1. It could be suggested that the H2S, as a major active compound in the mineral water, has the potential to modulate the gene expression of the investigated enzymes. Conclusion: Sulfurous mineral water should be considered an important dietary source of sulfur. We believe that the presented results would be of interest to society and health professionals.